Noncentrosymmetric Cation Order in the Cubic Perovskite Ba(4)CaFe(3)O9.5 - Turp, SA; Hargreaves, J; Baek, J; Halasyamani, P; Hayward, M (2010)
The syntheses and characterization of the acentric, B-cation ordered phase Ba4CaFe3O9.5 and a topotactically oxidized product Ba4CaFe3O10.7 are reported. Utilizing electron diffraction and neutron powder diffraction data, cation ordered structures based on a cubic perovskite lattice were refined for Ba 4CaFe3O9.5 (space group I212 121, a = 8.234(1) Å, b = 8.213(1) Å, c = 34.622(7) Å) and Ba4CaFe3O10.7 (space group I4̄2d a = 8.1821(4) Å, c = 32.3105(19) Å) The two Ba 4CaFe3O12-x phases exhibit complex structures in which Ca2+ and Fe3+ are ordered over the B-sites of the cubic perovskite lattice. This order results in the loss of structural inversion symmetry, thus the resulting cation ordered Ba4CaFe 3O12-x phases are both magnetic and acentric making them good candidates for multiferroic behavior. Further structural analysis reveals the complex cation order is induced through a combination of factors: the different coordination preferences of Ca2+ and Fe3+, anion vacancy ordering, and the need to minimize lattice strain. The general applicability of this synthetic strategy for the preparation of cation ordered materials is discussed. © 2010 American Chemical Society.